Bile Duct Injuries Associated with Laparoscopic and Open Cholecystectomy - Mihăileanu, Florin; Zaharie, Florin; Mocan, Lucian; Iancu, Cornel; Vlad, Liviu (Medicine and Pharmacy Reports, 2014)
Objectives. The aim of the study is to present the difficulties in the treatment of the biliary lesions and the methods for curing them, by presenting the surgical experience of a single surgeon from a tertiary care centre with experience in hepatic – biliary surgery. Material and method. A retrospective study was conducted during 1993-2008 on a sample of 71 patients with iatrogenic biliary lesions, operated in Surgical Clinic No 3 of Cluj-Napoca by the same surgeon. The patients were divided in two categories depending on the type of biliary lesion, as their majority came from other surgical departments. Results. 53.2% of the patients with biliary lesions of the studied sample suffered a surgical intervention for acute cholecystitis. 95.8% were represented by major biliary lesions, D-E classes with preponderance in female biliary lesions (F/M=3.4/1). The mean hospitalization range was 16 days. The post-surgery complications represented 10 cases of plague suppuration, 3 cases of anastomotic fistulas and 4 deaths. 80% of the patients who had complications, had previously an attempt of surgical treatment. The complications ratio was higher in these patients. The presence of hepatocytolisis and cholestasis as well as the anemia has influenced complications occurrence. Conclusions. The hepatic-jejunostomy is the main surgical approach in biliary lesions patients when other curing methods have failed. The optimum surgery time, the surgical technique and the surgical team experience are essential in treatment success.